Private security companies : transforming politics and security in the Czech Republic - Bureš, Oldřich, 1979- (Palgrave Macmillan, 2015)
This study presents intriguing analysis of the impact of private security companies' practices upon the fields of security and politics in the Czech Republic. It situates cases concerning ABL, the biggest Czech private security company, in the larger social, political, legal and economic contexts of the booming private security business. This company's extensive linkages with Czech politics suggest that the continued absence of specific legislation for the regulation of private security companies' activities is due to too much, rather than too little, political interest in their activities. This is problematic, arguably, because the practices of private security companies have already contributed to a significant transformation of the Czech security field by enhancing the commodification and depoliticization of security, while ABL's use of security methods for political purposes and a business approach to politics have profoundly transformed the field of politics. Reflecting the growing interest in the privatization of security, this timely study unpacks the relationship between politics, business and security in the Czech Republic.--Resumé vydavatele
Keywords: bezpečnostní služby -- Česko; security services -- Czechia; studie; elektronické knihy; studies; electronic books